Phosphorus management for tropical acid soils using amendments from agro-industrial wastes - Ch'ng, Huck Ywih (2015)
Phosphorus (P) deficiency in tropical acid soils is a problem because soluble inorganic phosphorus is fixed by aluminium (Al) and iron (Fe). Organic amendments could be used to overcome P fixation in acid soils. Thus, the objectives of this study were to: (i) produce organic amendments from agro-industrial wastes through co-composting; (ii) improve soil P availability by amending phosphate fertilizers with organic amendments; (iii) determine if the use of organic amendments could improve nutrients uptake, dry matter production, and yield of Zea mays L. cultivation on a tropical acid soil; and (iv) determine the economic viability of amending phosphate fertilizers with organic amendments in maize cultivation on a tropical acid soil. Compost was produced by mixing 20 kg of shredded pineapple leaf residues + 2 kg of chicken feed + 15.5 L of chicken manure slurry + 1 kg of molasses in each polystyrene box and these ratios apply to sago bagasse too. The composts produced had no foul odour, low heavy metals contents, and they had the desired amount of nutrients. To evaluate the quality of the compost produced, an incubation study was carried out for 90 days. Amending P fertilizers with the organic amendments significantly increased the soil pH to near neutral such that exchangeable Al and iron Fe which normally fix soil P were reduced, thus improved the P availability in acid soil. After the incubation study, a pot trial was conducted in a net house so as to evaluate the effects of treatments on maize growth performance in a controlled environment. The test crop used in this study was Thai Super Sweet hybrid F1 maize (Zea mays L.). The results of pot trial showed that amending chemical fertilizers (N-P-K) with the organic amendments improved Zea mays L. nutrients uptake and dry matter production. To further evaluate the promising treatments of the pot trial, a field experiment consisting of two maize planting cycles were carried out. The treatments with chemical fertilizers amended with organic amendments increased soil P availability and Zea mays L. yield in both cycles of planting. A follow up study of the field trial was embarked on to assess the effect of the organic amendments on P sorption and desorption. The results showed that more P was desorbed onto acidic soils with the presence of organic amendments as P application rates increased. The decrease in P sorption was due to the precipitation of exchangeable Al and Fe at the highly negatively charged humic substances functional group surfaces of the organic amendments due to increase in soil pH. To determine the economic viability of amending P fertilizers with organic amendments, an economic viability study was carried out. Net present value (NPV) was used to compute the viability of the different maize cultivation practices. Although the production cost of application of chemical fertilizers only are lower compared to amending chemical fertilizers with organic amendments, the ability of P fertilizer amended with pineapple leaf residues compost to improve soil chemical properties, increase yield and revenue indicate more economic viability.